2011
DOI: 10.1111/j.1440-0960.2011.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs surgery in Australia: A survey of work practices

Abstract: Australian Mohs surgeons make an important contribution to the management of skin cancer in Australia and many are skilled in laser and cosmetic procedures. The increasing number of cases performed annually and the familiarity with laser and cosmetic therapies reinforces Australian dermatologists as leaders in these important areas of dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
4
11
0
Order By: Relevance
“…Also, data from the Australian MMS Database showed that in 2007, tumors different from BCC and SCC represented only 1.13% of the total MMS performed that year . Moreover, in a national survey in Australia, Mohs surgeons reported that in 2011, cases other than BCC or SCC represented 2% of their practice . Similar to our series, where these tumors represent 1.8% of the total MMSs performed, a Dutch group reported the experience of a single center treating rare cutaneous tumors, which represented 2% of their series, although in this case DFSP was included …”
Section: Discussionsupporting
confidence: 80%
“…Also, data from the Australian MMS Database showed that in 2007, tumors different from BCC and SCC represented only 1.13% of the total MMS performed that year . Moreover, in a national survey in Australia, Mohs surgeons reported that in 2011, cases other than BCC or SCC represented 2% of their practice . Similar to our series, where these tumors represent 1.8% of the total MMSs performed, a Dutch group reported the experience of a single center treating rare cutaneous tumors, which represented 2% of their series, although in this case DFSP was included …”
Section: Discussionsupporting
confidence: 80%
“…The SCFA is a tertiary referral centre and those cases referred for MMS at the SCFA are typically the most complex cases of BCC; those with high-risk histological subtypes, those in anatomically challenging areas, and those who have failed TE previously. 9 Accordingly there is selection bias in the cases included in this study as they represent the most challenging cases of BCC surgically, accounting for the relatively high rate of incomplete excisions noted in the hypothetical TE arm compared with those previously reported in the literature ranging from 10% to 30%. 10,11 As the skin cancer capital of the world, Australian dermatologists are well versed in the surgical management of BCC and the choice of closures used this …”
Section: Discussionmentioning
confidence: 99%
“…From our responses the gender composition within MMS surgery continues to have an overall male preponderance, as has been demonstrated elsewhere, but that does significantly vary by country of practice with the Netherlands respondents identifying as 71.4% female (Table 2). 5,10–12 Notably, respondents were also provided the option of not declaring their gender or of reporting a nonbinary option (total 4.4%; 5 of 114). Notably in the USA, over a third of the American College of Mohs Surgeons (ACMS) members and roughly 50% of ACMS fellows are female 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas in the UK (75%) and Australia (85%), fellowship‐trained Mohs surgeons were the predominant respondents, the Dutch respondents had a significantly different composition and were equally as likely to have received their MMS training during residency (42.9%) as they were to have had formal fellowships (42.9%) (Table 2). Certainly in the UK and Australia, fellowship training is now the established route of training for MMS surgery 5,12 . Overall, the survey attracted respondents with a good range of experience, with both recently qualified Mohs surgeons and a handful of veteran Mohs surgeons with over 30+ years experience represented (Table 2).…”
Section: Discussionmentioning
confidence: 99%